The reluctant hegemon: India's self-perception and the South Asian strategic environment - Mitra, Subrata Kumar (Contemporary South Asia, 2003)
This article argues that the hiatus between India's self-perception as a status quo power and its perception by the neighbouring states as a regional bully is a main cause of stalemate in the South Asian security environment. This main argument is analysed in terms of the appurtenances of Indian power, the pronouncements of its statesmen, the perception of its voters and strategists, and the institutional arrangement of its security apparatus. Greater cohesion in the country's strategic perception will enhance the transformation of India's potential strength into an effective role in South Asian security.
Published online: 20 Jan 2011
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 22.06.2021
Keywords: Indien; Südasien